miRNA Regulation of NK Cells Antiviral Response in Children With Severe and/or Recurrent Herpes Simplex Virus Infections - Lenart, Marzena; Działo, Edyta; Kluczewska, Anna; Węglarczyk, Kazimierz; Szaflarska, Anna; Rutkowska-Zapała, Magdalena; Surmiak, Marcin; Sanak, Marek; Pituch-Noworolska, Anna; Siedlar, Maciej (Frontiers in Immunology, 2021)
Severe and/or recurrent infection with HSV is observed in a large group of patients treated in clinical immunology facilities. Atypical and prolonged HSV infection is the most common clinical manifestation of disturbed NK cell development and functions, yet the molecular basis of these disorders is still largely unknown. Since recent findings indicated the importance of miRNA in regulating NK cell development, maturation and functions, the aim of the project was to investigate miRNA expression pattern in NK cells in patients with severe and/or recurrent infections with Herpes simplex virus and study the role of these miRNAs in NK cell antiviral response. As a result, miRNA expression pattern analysis of human best known 754 miRNAs revealed that patients with severe and/or recurrent HSV infection had substantially upregulated expression of four miRNAs: miR-27b, miR-199b, miR-369-3p and miR-491-3p, when compared to healthy controls. Selective inhibition of miR-27b, miR-199b, miR-369-3p and miR-491-3p expression in NK-92 cells resulted in profound upregulation of 4 genes (APOBEC3G, MAP2K3, MAVS and TLR7) and downregulation of 36 genes taking part in antiviral response or associated with signaling pathways of Toll-like receptors (TLR), NOD-like receptors, the retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) and type I IFN-related response. Additionally, flow cytometry analysis revealed that miR-369-3p and miR-491-3p inhibitors downregulated NK cell intracellular perforin expression, while the expression of granzyme B and IFNγ remained unchanged. Taken together, our study suggests a novel mechanism which may promote recurrence and severity of HSV infection, based on miRNAs-dependent posttranscriptional regulation of genes taking part in antiviral response of human NK cells.